2010
DOI: 10.1161/circimaging.109.920538
|View full text |Cite
|
Sign up to set email alerts
|

Iodine-123 Metaiodobenzylguanidine Imaging and Carbon-11 Hydroxyephedrine Positron Emission Tomography Compared in Patients With Left Ventricular Dysfunction

Abstract: Background— Although both 123 I-metaiodobenzylguanidine ( 123 I-MIBG) imaging and 11 C-hydroxyephedrine ( 11 C-HED) positron emission tomography (PET) are used for assessing cardiac sympathetic innervation, their relationship remains unknown. The aims were to determine whether 123 I-MIBG parameters such as heart-to-mediastinum ratio (H/M) are ass… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
42
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 71 publications
(42 citation statements)
references
References 34 publications
0
42
0
Order By: Relevance
“…Moreover, the predictive value of late [ 123 I]MIBG defect was confirmed for appropriate ICD therapy in a more recent study 11. Although the [ 11 C]HED PET defect size is closely related to the early and late [ 123 I]MIBG SPECT defect size, it provides superior spatial resolution and potential for absolute quantification 28. The PAREPET study demonstrated that the total size of cardiac denervation predicted appropriate ICD therapy, independent of LVEF, infarct volume and hibernating myocardium.…”
Section: Discussionmentioning
confidence: 90%
“…Moreover, the predictive value of late [ 123 I]MIBG defect was confirmed for appropriate ICD therapy in a more recent study 11. Although the [ 11 C]HED PET defect size is closely related to the early and late [ 123 I]MIBG SPECT defect size, it provides superior spatial resolution and potential for absolute quantification 28. The PAREPET study demonstrated that the total size of cardiac denervation predicted appropriate ICD therapy, independent of LVEF, infarct volume and hibernating myocardium.…”
Section: Discussionmentioning
confidence: 90%
“…Short-axis images were used to define a region of interest in the left ventricle. Myocardial 11 C-HED uptake was expressed using the retention index (RI [min 21 ]) that was calculated as the mean myocardial activity in the last frame (30-40 min) divided by the integral of the arterial blood time-activity curve derived from a manually placed region of interest at the basal LV cavity of valve plane (19,20). Regional PET analyses were based on the American Heart Association 17-segment model.…”
Section: Discussionmentioning
confidence: 99%
“…However, the heart-to-mediastinum ratio on early and delayed planar images and washout rate derived from 123 Imetaiodobenzylguanidine imaging were semiquantitative. In contrast, 11 C-HED is a high-specific-activity PET tracer for SNS presynaptic imaging (19) and enables better regional analysis than 123 I-metaiodobenzylguanidine (20).…”
Section: Discussionmentioning
confidence: 99%
“…Rischpler et al (75) reported that the 131 I-MIBG uptake defect in rats matched the area of an earlier MI, whereas the mHED uptake defect was larger. However, in a direct comparison of 123 I-MIBG SPECT and mHED PET in 21 patients with left ventricular dysfunction, Matsunari et al (76) reported a high correlation between defect sizes in the 2 methods; however, late 123 I-MIBG SPECT overestimated defect sizes in the inferior and septal regions, presumably because of image quality issues caused by adjacent liver activity.…”
Section: Comparison Of Spect and Pet Techniquesmentioning
confidence: 99%